Lectures on Dostoevsky - Frank, Joseph, 1918-2013 (Princeton University Press, 2020)
"This book collects twelve classroom lectures on seven major works by Dostoevsky--Crime and Punishment, The Brothers Karamazov, The Idiot, Notes from Underground, and three others--by Joseph Frank, the author of the definitive five-volume biography of Dostoevsky published by Princeton University Press. Frank's widow, Marguerite Frank, has worked with a Russian translator and former student of Frank's, Marina Brodskya, to compile the lectures--some of which Frank had written out in their entirety, others for which he left extensive notes. The book will contain a preface, introduction, seven chapters (each containing one or two lectures on a major work), and lists of further reading and stage and screen adaptations of Dostoevsky's works. Each lecture is about 4,000 words and is written in a conversational style that is accessible for undergraduates but also demonstrates Frank's unparalleled knowledge of the Russian author and his world, providing wide-ranging literary and historical context. The editors include notes to explain references and allusions. The book also will include some images of Joseph Frank, Dostoevsky, a couple of artworks discussed in the lectures, and a sample of Frank's handwritten lecture notes"--